Cultural diversity in organizational communication management at English course in Vietnam - Meltareza, Ridma; Wiryany, Detya (Faculty of Communication Sciences Universitas Padjadjaran, 2024)
English serves as the global lingua franca, facilitating communication and bridging cultural differences worldwide. Its significance in various sectors, such as business, technology, science, and media, solidifies its position as a universal means of communication. This study explores the increasing importance of English in Vietnam, particularly in major cities like Hanoi, where it plays a crucial role in business, tourism, and higher education. The focus is on Mercury Center, a prestigious language institution in Hanoi, which collaborates with foreign travelers as volunteer teachers to enhance Vietnamese citizens’ English proficiency. Using qualitative research methods, including interviews, direct observations, and literature reviews, the study assesses the impact of foreign volunteer teachers on language education in Vietnam. It reveals that students and parents highly value and trust foreign teachers for their perceived authenticity and expertise in English. These findings underscore the significance of cultural diversity in English language education. By embracing foreign volunteer teachers and creating a cross-cultural learning environment, language institutions like Mercury Center can provide a more enriching and impactful learning experience for Vietnamese students. Understanding and managing cultural diversity can lead to improved communication and contribute to the success of language education initiatives in Vietnam. The recommendation from these findings is to optimize the utilization of cultural diversity within educational institutions to enhance organizational performance, create an inclusive work environment, and improve workgroup efficiency by considering consumer preferences and needs while developing more effective marketing strategies.